Legal but corrupt a new perspective on public ethics - Anechiarico, Frank (Lanham, Maryland Lexington Books, 2017)
"Labeling a person, institution or particular behavior as 'corrupt' signals both political and moral disapproval and, in a functioning democracy, should stimulate inquiry, discussion, and, if the charge is well-founded, reform. This book argues...that the political community and scholars alike have underestimated the extent of corruption in the United States and elsewhere and thus, awareness of wrong-doing is limited and discussion of necessary reform is stunted. In fact, there is a class of behaviors and institutions that are legal, but corrupt. They are accepted as legitimate by statute and practice, but they inflict very real social, economic, and political damage. This book explains why it is important to identify legally accepted corruption and provides a series of examples of corruption using this perspective."-- Back cover.
1: Introduction: What’s Corrupt?, Frank Anechiarico -- 2: Doubling Down on Derivatives: The Legal but Corrupt Exploitation of the Fallout from the Great Recession, Danny L. Balfour and Guy B. Adams -- 3: Shaping the State to Private Purposes: A Comparison of Conflicts of Interest in the United States and Sweden, Staffan Andersson and Frank Anechiarico -- 4: Whose Corruption? Which Law? Law’s Authority and Social Power, Ciarán O'Kelly -- 5: Racialized Policing in New York City: The NYPD and Stop, Question, Frisk, Frank Anechiarico -- 6: Benefit Corporations: A Solution to the Crisis of Corporate Legitimacy?, Lydia Segal -- 7: Inclusion, Accountability and the Reform of Legal Corruption, Frank Anechiarico -- Appendix A: The Politics of the Swedish Nursing Home Scandal -- Appendix B: Benchmark Analysis from the Rand Study -- Appendix C: Conceptual Inventory -- Index -- About the Contributors
Includes bibliographical references and index.
Keywords: Political corruption -- United States; Misconduct in office -- United States; Public administration -- Moral and ethical aspects; Political ethics -- United States